Beyond the dinner table: who's having breakfast, lunch and dinner family meals and which meals are associated with better diet quality and BMI in pre-school children?. Issue 18 (14th September 2017) - Berge, Jerica M; Truesdale, Kimberly P; Sherwood, Nancy E; Mitchell, Nathan; Heerman, William J; Barkin, Shari; Matheson, Donna; Levers-Landis, Carolyn E; French, Simone A
Abstract: Objective: Having frequent family dinners is associated with better diet quality in children; however, it is unknown whether the frequency of certain family meal types (i.e. dinner) is more strongly associated with better child weight and diet quality compared with other meal types (i.e. breakfast, lunch). Thus, the current study examined the frequency of eating breakfast, lunch or dinner family meals and associations with pre-school children's overall diet quality (HEI-2010) and BMI percentile. Design: Cross-sectional baseline data (2012–2014) from two randomized controlled childhood obesity prevention trials, NET-Works and GROW, were analysed together. Setting: Studies were carried out in community and in-home settings in urban areas of Minnesota and Tennessee, USA. Subjects: Parent–child (ages 2–5 years) pairs from Minnesota ( n 222 non-Hispanics; n 312 Hispanics) and Tennessee ( n 545 Hispanics; n 55 non-Hispanics) participated in the study. Results: Over 80 % of families ate breakfast or lunch family meals at least once per week. Over 65 % of families ate dinner family meals ≥5 times/week. Frequency of breakfast family meals and total weekly family meals were significantly associated with healthier diet quality for non-Hispanic pre-school children ( P <0·05), but not for Hispanic children. Family meal frequency by meal type was not associated with BMI percentile for non-Hispanic or Hispanic pre-school children. Conclusions: Breakfast family meal frequency and total weekly family meal frequency were associated with healthier diet quality in non-Hispanic pre-school children but not in Hispanic children. Longitudinal research is needed to clarify the association between family meal type and child diet quality and BMI percentile.